2013
DOI: 10.1016/j.actatropica.2013.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal-praziquantel: Efficacy against Schistosoma mansoni in a preclinical assay

Abstract: Currently, schistosomiasis mansoni is treated clinically with praziquantel (PZQ). Nevertheless, cases of tolerance and resistance to this drug have been reported, creating the need to develop new drugs or to improve existing drugs. Considering the small number of new drugs against Schistosoma mansoni, the design of nanotechnology-based drug delivery systems is an important strategy in combating this disease. The aim of this study was to evaluate the activity of PZQ containing liposome (lip.PZQ) on S. mansoni, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 33 publications
4
14
0
1
Order By: Relevance
“…Moreover, liposome‐entrapped drugs provided protection over a much broader time window . Similar effects were also confirmed with other drugs, including PZQ and DEC, in later studies . Here the observed improvement in therapeutic efficacy using liposome encapsulated drugs can be explained by greater bioavailability and longer circulation of the drugs as they are loaded in liposomes.…”
Section: How Can Nanodelivery Systems Transform the Treatment Of Helmsupporting
confidence: 69%
See 1 more Smart Citation
“…Moreover, liposome‐entrapped drugs provided protection over a much broader time window . Similar effects were also confirmed with other drugs, including PZQ and DEC, in later studies . Here the observed improvement in therapeutic efficacy using liposome encapsulated drugs can be explained by greater bioavailability and longer circulation of the drugs as they are loaded in liposomes.…”
Section: How Can Nanodelivery Systems Transform the Treatment Of Helmsupporting
confidence: 69%
“…Here the observed improvement in therapeutic efficacy using liposome encapsulated drugs can be explained by greater bioavailability and longer circulation of the drugs as they are loaded in liposomes. It has been also speculated that the drug molecules may be absorbed more effectively by parasites, as liposomes dock on and fuse with worms' outermost surface, but further investigation of the idea may be required.…”
Section: How Can Nanodelivery Systems Transform the Treatment Of Helmmentioning
confidence: 99%
“…An increase of 2 to 4 times the concentration of PZQ in the incubation medium did not change the amount of absorbed PZQ, indicating an increased saturation concentration gradient. Frezza et al 17 observed that the PZQ dose previously tested for the LE strain (Mourão et al 2005) did not show the same activity when employed in mice infected with the S. Mansoni BH strain. Increasing the dose of PZQ improved schistosomicidal activity, and PZQ encapsulated in liposomes was more effective than an equivalent dose of free PZQ, inhibiting oviposition and hepatic granuloma formation.…”
Section: Introductionmentioning
confidence: 90%
“…These drugs may have greater bioavailability in the host, and they may be better absorbed by the tegument of S. mansoni, which has an affinity for phospholipids. 17 Campos et al 18 developed a Dextran-70 hydrogel for the controlled release of PZQ and performed in vitro release assays. They observed that the release profile of PZQ was prolonged by incorporation into dextran molecules.…”
Section: Introductionmentioning
confidence: 99%
“…These formulations have gained significance as nanocarriers in helminthic infection due to their ability to diffuse through the intestinal mucosal layers. In schistosomiasis, liposome encapsulated praziquantel has shown significant reductions in parasitic burdens and hepatic granulomas due to increased affinity for parasite phospholipids [130]. Liposome based nanocapsules of praziquantel (PZQ-LNCs) improved the drug efficacy and ameliorated disease pathology [131].…”
Section: Nano-medicinal Approachmentioning
confidence: 99%